Microstructural Characterization of 3D Printed NiMnGaCoCu Based Magnetic Shape Memory Alloys - A. Wójcik; R. Chulist; A. Szewczyk; B. Morończyk; Ł. Żrodowski; R. Wróblewski; M. Kowalczyk; W. Maziarz (Archives of Metallurgy and Materials)
The main aim of this research was to produce, by laser powder bed fusion (LPBF) process, good quality material with nonmodulated martensite structure exhibiting high magnetic field-induced strain value. The microstructure and texture of NiMnGaCoCu alloy were investigated by SEM, TEM, and high-energy X-ray diffraction. It was shown that LPBF process combined with the postprocessing annealing allowed to obtain a homogeneous microstructure with a strong <100> fiber texture along the growth direction. It was also shown that the scanning strategy does not greatly affect the microstructure and crystal structure of the material while the only difference lies in the existence of a double texture component for alloy produced by oscillating mode. Finally, the magnetic field-induced strain value calculated for the alloy with non-modulated martensite produced by the 3D printing was about 0.2%.